Front Cover: The Photophysics of Dibenzo[a, j]phenazine (4/2021). Issue 4 (20th April 2021) - Thom, Kristoffer A.; Förster, Tom; Weingart, Oliver; Goto, Shimpei; Takeda, Youhei; Minakata, Satoshi; Gilch, Peter
Abstract : The Front Cover depicts the first author Kristoffer Thom explaining, with the aid of a blackboard, the results of a collaboration between HHU Düsseldorf (Germany) and Osaka University (Japan) on the photophysics of dibenzo[ a, j ]phenazine. This compound is of great interest for organic electronics and photonics. More information can be found in the Article by Oliver Weingart, Youhei Takeda, Peter Gilch and co‐workers .